Prevalence and Risk Factors of Transfusion‐Transmissible Infections Among Voluntary Blood Donors in North Shoa, Amhara Region, Ethiopia: A Cross‐Sectional Study - Demissew Shenkute Gebreyes; Kifle Kifetew; Aragaw Gizaw; Tsegahun Asfaw Abebe; Tassew Tefera Shenkutie; Deribew Genetu; Berhanu Yitayew; Awraris Hailu (Health Science Reports)
ABSTRACT Background and Aim Transfusion‐transmissible infections (TTIs) pose a significant threat to patients requiring blood transfusion. The prevalence of TTIs among blood donors reflects the broader burden of infections within populations. Therefore, assessing the prevalence of TTIs among voluntary blood donors is crucial for informing effective prevention and control strategies in the community. Study Design and Methods A cross‐sectional study was conducted from April 2022 to July 2022. Sociodemographic and related data were collected using a pre‐tested structured questionnaire. A venous blood sample (5 mL) was drawn from each blood donor into sterile test tubes, and serum was separated through centrifugation. The serum samples were tested using enzyme‐linked immunosorbent assays (ELISA) to detect hepatitis B Virus (HBV), hepatitis C virus (HCV), human immunodeficiency virus (HIV), and syphilis. Data analysis was performed using SPSS version 25 and summarized in tables and figures. Results A total of 538 participants were enrolled in the study, with an overall prevalence of transfusion‐transmissible infections (TTIs) at 7.4% (n = 40). Syphilis exhibited the highest prevalence at 3% (n = 16), followed by HBV at 2% (n = 11). The prevalence of HCV and HIV was 1.3% (n = 7) and 1.1% (n = 6), respectively. Significant factors associated with HBV seroprevalence included the donation site at Debre Berhan [AOR = 24.18, 95% CI: 1.98–295.14, p = 0.01] and the presence of body tattoos [AOR = 19.1, 95% CI: 4.0–89.8, p ≤ 0.01]. Male sex was significantly associated with syphilis infections [AOR = 3.78, 95% CI: 1.23–11.61, p = 0.03]. Conclusions This study highlighted the high prevalence of TTIs among blood donors. To prevent and control the transmission of TTIs within the population, strict donor screening protocols, improved diagnostic methods, and enhanced awareness about infection transmission should be implemented.